2018
DOI: 10.3856/vol46-issue1-fulltext-8
|View full text |Cite
|
Sign up to set email alerts
|

Production and management of shrimp (Penaeus vannamei) in co culture with basil (Ocimum basilicum) using two sources of low salinity water

Abstract: ABSTRACT. The aim of this study was to evaluate the production of an aquaponic culture of white shrimp (Penaeus vannamei) and basil (Ocimum basilicum) using two sources of low-salinity water (1.7 g L ), no significant differences (P > 0.05) were found for the final individual weight, survival, growth rate and feed conversion ratio between DSW and GW, whereas for basil, lower yields were found with DSW. No significant differences in the basil production between the control and the treatment GW were found. Feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It has been demonstrated that fish grown in an aquaponic system have normal growth and survival compared to traditional production methods. Some of the species successfully grown aquaponically include largemouth bass (Micropterus salmoides) [20], channel catfish (Ictalurus punctatus) [24], Nile tilapia (Oreochromis niloticus) [25], rainbow trout (Oncorhynchus mykiss) [26,27], goldfish (Carassius auratus) [28], and white shrimp (Litopenaeus vannamei) [29]. In this study, the fish growth was acceptable and similar to the production parameters in other reports [30][31][32][33] and the tilapia growth was not adversely affected by the frass type.…”
Section: Discussionsupporting
confidence: 56%
“…It has been demonstrated that fish grown in an aquaponic system have normal growth and survival compared to traditional production methods. Some of the species successfully grown aquaponically include largemouth bass (Micropterus salmoides) [20], channel catfish (Ictalurus punctatus) [24], Nile tilapia (Oreochromis niloticus) [25], rainbow trout (Oncorhynchus mykiss) [26,27], goldfish (Carassius auratus) [28], and white shrimp (Litopenaeus vannamei) [29]. In this study, the fish growth was acceptable and similar to the production parameters in other reports [30][31][32][33] and the tilapia growth was not adversely affected by the frass type.…”
Section: Discussionsupporting
confidence: 56%
“…The production of P. vannamei is carried out mainly in coastal areas, however, in recent years it has expanded to locations far from the coast and in low salinity conditions (Roy et al 2010a;Fierro et al 2018). This can be related to the various economic and environmental advantages presented in these regions when compared to coastal zones, such as lower cost of land acquisition, less con icts arising from the use of common resources, and reduced impact on not very resilient ecosystems such as mangroves (Jory 2017; Lacerda et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The species ability to thrive in a salinity range from 0.5 to 45 g L -1 , in waters with an adequate ionic balance, make it a viable alternative for culture in diverse aquatic environments (González-Félix et al, 2017), since it has been farmed in waters from wells as well as in salinized land unable for agriculture (Páez-Osuna & Valencia-Castañeda, 2013;Jarwar, 2015). Moreover, due to the negative effect that _________________ Corresponding editor: Fernando Vega marine aquaculture has had as a result of various viral diseases, the inland farming of marine organisms has become a viable alternative (Fierro et al, 2018). However, the culture at low salinities faces some challenges, some of them related to nutrition and environmental sustainability (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%